EFFECT OF FIVE WEEK ASANA TRAINING ON FLEXIBILITY OF WOMEN PLAYERS - Kumar, Sanjeev; Monika Saini (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
Yoga is also very important in our life, both yoga and sports are important for us. Yoga is a physical, mental and spiritual practice that originated in ancient India. The word yoga is derived from the Sanskrit root yuj, meaning “to yoke,” or “to unite”. The practice aims to create union between body, mind and spirit, as well as between the individual self and universal consciousness. The present study was under taken on 60 subjects (gymnastics, wrestling and Kabaddi women players). Which are equally divided experimental group (N-30) and controlled group (N-30) using sit and reach test for flexibility was measured by before and after the training period of five weeks. During experimental period it was observed by the researcher that the subjects belonging to experimental group practiced yogic activities for five weeks. Subject was shown significant improvement in their flexibility in comparison to the controlled group. Hence it is concluded yogic exercises for five weeks bring significant difference in flexibility.